Maintaining Language Politeness Through Learning Advice in Japanese - Rahayu, Poppy; Suryadi, Dedi; Rinjani, Rosita (Universitas Pendidikan Indonesia (Indonesia University of Education), 2020)
In the world of education, the ability and sensitivity in delivering advice is needed. This is because advice is a speech that is very often used in interactions with students in building character. With regard to various important factors that must be considered in delivering speech advice, especially in learning foreign languages which may have different speech cultures. This research aims to obtain an overview how the speakers maintaining politeness in advice utterance. The maintaining politeness of advice in terms of strategy, use of modifications, in term of politeness principle, in term of cooperative principle, type of expression and variety of language used in advice utterance, so it is hoped that used as instruments in maintaining politeness in the concept of learning. This research is based on a qualitative paradigm, with content analysis techniques and inductive procedures. Sharpening the focus of the study in this research is on its pragmatic competence. Based on the research results, it can be concluded that the way to maintain politeness in speaking is to use a speech strategy, either directly or indirectly, followed by modifications in the speech. In giving advice, the most priority to pay attention to by speakers is the interests and benefits of the interlocutors, then sympathy for the interlocutors, then in giving advice, not to be arrogant, not criticizing the interlocutors and as much as possible praising the interlocutors, and to avoid disapproval of the interlocutors. Then in carrying out the conversation the speaker expresses what is needed, is relevant to the conversation, speaks the right thing, and speaks clearly. In addition to the use of these expressions and speech strategies, when delivering speeches, the ways of maintaining politeness also pay attention to the mental or psychological condition of the interlocutors.